Maoist People’s War and Its Socio-Economic Impacts in Peru - Nepal, Mani (Economic Journal of Development Issues, 2010)
This paper analyzes a period of significant violence in Peru, from 1980 to 2000. Historical data suggest that the roots of the armed struggle lie in poverty, inequality, and ethnic grievances. During this period, over 69,000 people died or disappeared, the economy stagnated, and per capita income growth was negative. In the public sector, education and health suffered the largest declines in spending. Inflation surged out of control during 1989-1992. After the capture of the Shining Path leader in 1992, the intensity of armed conflict declined. The Peruvian economy regained its momentum, and inflation was brought under control. On the political front, greater stability was attained. However, lawlessness continued to be the major problem in post-conflict Peru and the underlying causes that prompted the civil war have not been fully addressed. This raises the possibility that violent conflict could return anytime in future. Key words: Maoist People’s war; Violent conflict; Peru; Armed struggle; Revolutionary Left Movements Economic Journal of Development Issues Vol. 9 and 10 (2008 & 2009) Combined Issue Page: 59-76